2017
DOI: 10.1007/s10164-017-0520-1
|View full text |Cite
|
Sign up to set email alerts
|

Plant architectural traits influence residence time of a specialist jumping spider

Abstract: The patch residence time of spiders has long been attributed to prey availability. We provide empirical evidence that plant architecture determines the residence time of a bromeliad-living spider. The residence time of spiders was longer on rosette-shaped plants. Males left their host plant faster than females, likely due to their mate-searching activity. We demonstrate that plant architectural traits mediate the patch-leaving tendency of specialist spiders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Gonçalves-Souza et al (2014) showed that spiders with more compressed bodies were associated with bromeliads with greater leaf length. Number of leaves might be one of the most distinguishable traits, as spiders such as Salticidae can select their host plant using visual cues (de Omena & Romero, 2010;de Omena et al, 2017). Moreover, other studies have found that these plant traits adequately predict the spatial distribution of spiders on bromeliads (e.g.…”
Section: Bromeliad and Spider Morphological Traitsmentioning
confidence: 99%
“…Gonçalves-Souza et al (2014) showed that spiders with more compressed bodies were associated with bromeliads with greater leaf length. Number of leaves might be one of the most distinguishable traits, as spiders such as Salticidae can select their host plant using visual cues (de Omena & Romero, 2010;de Omena et al, 2017). Moreover, other studies have found that these plant traits adequately predict the spatial distribution of spiders on bromeliads (e.g.…”
Section: Bromeliad and Spider Morphological Traitsmentioning
confidence: 99%